Identification of Two Duplicated Loci Controlling a Disease‐like Rugose Leaf Phenotype in Soybean. Issue 4 (1st July 2016) - Wang, Yaqi; Chen, Wei; Zhang, Ye; Liu, Meifeng; Kong, Jiejie; Yu, Zheping; Jaffer, Ali M.; Gai, Junyi; Zhao, Tuanjie
Abstract : The disease‐like leaf mutant exhibits sensitive symptoms in the absence of pathogens and is an important experimental material for studying leaf development and pathogen resistance mechanisms in plants. We used 60 Co γ ray irradiation treatment of a Japanese soybean [ Glycine max (L.) Merr.] plant introduction Tamahomore to obtain a new disease‐like mutant, designated NT301. The mutant leaves were significantly smaller and thicker than those of the wild‐type plant, with a reduction in leaf vein growth and increased growth of leaf mesophyll tissue. The surface of these rugose leaves resembled the symptoms of virus infection. Genetic analysis of two crosses between NT301 and the normal parents indicated that the rugose traits were controlled by two pairs of recessive duplicated genes, tentatively designated rl1 and rl2 . We mapped rl1 between simple sequence repeats (SSR) markers BARCSOYSSR_18_0415 and BARCSOYSSR_18_0485 on chromosome 18. We mapped rl2 between BARCSOYSSR 08_1700 and Satt409 on chromosome 8, a region that is homoeologous to the rl1 position. We have inferred the possible process for creation of this induced mutant with double recessive genes. Our study will facilitate the gene cloning of rl1 and rl2, providing a new genetic stock for exploring the genetic mechanisms of leaf development and genome evolution in soybean.